Problems in the South: Puno in the processes of transformation of Global Capitalism - Canaza-Choque, Franklin Américo (2021)
Past 1990, capitalism has developed a series of gears on its own and proper functioning as world-system, to renew as many times as you want in the face of a crisis that speculates its apocalyptic end. It is capital, first a decisive factor in production, and at the same time a power that does not obey any law on how things have been set and order in the world, it is like that, that the circumstances of the moment have been taken advantage of in some way by networks and economic knots capitalizers common goods. It is on this expansive molding of practical reasons that the economy puneña unfolds day by day, perhaps in the best way, where social relations, modes of production and local economic flows are sufficiently chained to fixed and concentrated economic growth rates in the primary sector, particularly, agricultural and mining, here, is where the big doses of world market strongly press. In this effort, the study analysis one of regions the country condemned to mining: Puno. Lake region, which over the years has become the focus of a huge capitalize chain of natural resources and territorial expropriation infinitely unsustainable.